(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
On September 1910, it was celebrated the first century of the independence, apotheosis of Díaz, months later the revolution was broken out. With the Plan de San Luis, Mexico had certain political and peace stability, celebrating the century of the consumption on 1921 independence, where several social groups manifested. Mexican Catholic Church was not alien to the actions related to this historical fact, rescuing its presence. The Mexican revolution, with Madero, was well spent by social Catholics to set up a political party that added itself to the trade unions, saving banks, schools and catholic press that recovered part of their old favorable conditions. For Catholics, the death of Madero and the presence of Carranza were both a hard time, stopping their projects as well as the expulsion from the country of several of their leaders, but the organizations’ plans survived. At the early 20´s social Catholicism emerged and with it returned the exiled Catholics and gathered again. With the religion celebrations and the celebrations of the century of the independence, spaces were taken by Mexican Catholic Church public giving a new impulse to their cause. In this paper, we consider the different actions taken by radical social Catholics, as well as having a better vision of the celebrations of the consumption of the independence in 1921.